Convergent evidence for the temperature-dependent emergence of silicification in terrestrial plants - Zhihao Pang; Félix de Tombeur; Sue E. Hartley; Constantin M. Zohner; Miroslav Nikolic; Cyrille Violle; Lidong Mo; Thomas W. Crowther; Dong-Xing Guan; Zhongkui Luo; Yong-Guan Zhu; Yuxiao Wang; et al. (Nature Communications)
Abstract Research on silicon (Si) biogeochemistry and its beneficial effects for plants has received significant attention over several decades, but the reasons for the emergence of high-Si plants remain unclear. Here, we combine experimentation, field studies and analysis of existing databases to test the role of temperature on the expression and emergence of silicification in terrestrial plants. We first show that Si is beneficial for rice under high temperature (40 °C), but harmful under low temperature (0 °C), whilst a 2 °C increase results in a 37% increase in leaf Si concentrations. We then find that, globally, the average distribution temperature of high-Si plant clades is 1.2 °C higher than that of low-Si clades. Across China, leaf Si concentrations increase with temperature in high-Si plants (wheat and rice), but not in low-Si plants (weeping willow and winter jasmine). From an evolutionary perspective, 77% of high-Si families (>10 mg Si g−1 DW) originate during warming episodes, while 86% of low-Si families (<1 mg Si g−1 DW) originate during cooling episodes. On average, Earth’s temperature during the emergence of high-Si families is 3 °C higher than that of low-Si families. Taken together, our evidence suggests that plant Si variation is closely related to global and long-term climate change.